2020
DOI: 10.1016/j.hrthm.2020.03.021
|View full text |Cite
|
Sign up to set email alerts
|

Left ventricular endocardial pacing is less arrhythmogenic than conventional epicardial pacing when pacing in proximity to scar

Abstract: Background Epicardial pacing increases risk of ventricular tachycardia (VT) in patients with ischemic cardiomyopathy (ICM) when pacing in proximity to scar. Endocardial pacing may be less arrhythmogenic as it preserves the physiological sequences of activation and repolarization. Objective The purpose of this study was to determine the relative arrhythmogenic risk of endocardial compared to epicardial pacing, and the role of the transmural gradient of action potential d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 26 publications
0
10
0
2
Order By: Relevance
“…In a canine LBBB model study, biventricular epicardial pacing, but not endocardial pacing, created a significant transmural dispersion of repolarization [ 16 ]. This is supported by a computational modeling study where the high repolarization gradients observed during epicardial pacing in close proximity to scar were not found during endocardial pacing [ 21 ]. How the observed effects on repolarization translate into risk of ventricular arrhythmia in clinical practice remains unclear; however, they suggest that endocardial LV pacing may be less arrhythmogenic than epicardial pacing, particularly in patients with ischemic cardiomyopathy.…”
Section: Potential Advantages Of Left Ventricular Endocardial Pacingmentioning
confidence: 63%
See 1 more Smart Citation
“…In a canine LBBB model study, biventricular epicardial pacing, but not endocardial pacing, created a significant transmural dispersion of repolarization [ 16 ]. This is supported by a computational modeling study where the high repolarization gradients observed during epicardial pacing in close proximity to scar were not found during endocardial pacing [ 21 ]. How the observed effects on repolarization translate into risk of ventricular arrhythmia in clinical practice remains unclear; however, they suggest that endocardial LV pacing may be less arrhythmogenic than epicardial pacing, particularly in patients with ischemic cardiomyopathy.…”
Section: Potential Advantages Of Left Ventricular Endocardial Pacingmentioning
confidence: 63%
“…Epicardial LV pacing reverses the physiological pattern of activation and repolarization within the myocardial wall, and has been demonstrated to increase the QT interval and transmural dispersion of repolarization in animal studies [ 19 , 20 ]. Increased local dispersion of repolarization has also been demonstrated during epicardial pacing in close proximity to scar in computational modeling studies [ 21 , 22 ]. However, while CRT-induced ventricular tachycardia has been reported [ 23 ], conventional CRT appears to have a significantly beneficial effect on the risk of ventricular arrhythmia, most likely due to the associated reverse LV remodeling.…”
Section: Potential Advantages Of Left Ventricular Endocardial Pacingmentioning
confidence: 99%
“…This may have also resulted in underrepresentation of ischemic patients who are generally regarded as more unwell than nonischemic patients as evidenced by only 45.5% of ischemic patients in this study, similar to the ALSYNC study that included 42.9% 8 . Ischemic patients have a greater potential to benefit from targeted endocardial pacing 14,16 . An accurate Simpson's biplane was not possible for all patients and a change in LVEF ≥5% was, therefore, used but it is appreciated that this is a less reliable estimate of outcome than reduction in LV systolic volume ≥15%.…”
Section: Limitationsmentioning
confidence: 91%
“…8 Ischemic patients have a greater potential to benefit from targeted endocardial pacing. 14,16 An accurate Simpson's biplane was not possible for all patients and a change in LVEF ≥5% was, therefore, used but it is appreciated that this is a less reliable estimate of outcome than reduction in LV systolic volume ≥15%.…”
Section: Limitationsmentioning
confidence: 99%
“…[ 6 9 ] Endocardial pacing is less arrhythmogenic than epicardial pacing and is less affected by myocardial scar location. [ 18 ] It is also less likely to result in phrenic nerve stimulation such as in epicardial pacing. The greatest potential benefit of endocardial pacing is the ability to pace anywhere inside the left ventricle, enabling the operator to select the optimal pacing site unrestricted by the coronary sinus anatomy.…”
Section: Endocardial Pacingmentioning
confidence: 99%